Heat Shock Protein 60, Insights to Its Importance in Histoplasma capsulatum: From Biofilm Formation to Host-Interaction - Fregonezi, Nathália Ferreira; Oliveira, Lariane Teodoro; Singulani, Junya de Lacorte; Marcos, Caroline Maria; dos Santos, Claudia Tavares; Taylor, Maria Lucia; Mendes-Giannini, Maria José Soares; de Oliveira, Haroldo Cesar; Fusco-Almeida, Ana Marisa (Frontiers in Cellular and Infection Microbiology, 2021)
Heat shock proteins (Hsps) are among the most widely distributed and evolutionary conserved proteins, acting as essential regulators of diverse constitutive metabolic processes. The Hsp60 of the dimorphic fungal Histoplasma capsulatum is the major surface adhesin to mammalian macrophages and studies of antibody-mediated protection against H. capsulatum have provided insight into the complexity involving Hsp60. However, nothing is known about the role of Hsp60 regarding biofilms, a mechanism of virulence exhibited by H. capsulatum. Considering this, the present study aimed to investigate the influence of the Hsp60 on biofilm features of H. capsulatum. Also, the non-conventional model Galleria mellonella was used to verify the effect of this protein during in vivo interaction. The use of invertebrate models such as G. mellonella is highly proposed for the evaluation of pathogenesis, immune response, virulence mechanisms, and antimicrobial compounds. For that purpose, we used a monoclonal antibody (7B6) against Hsp60 and characterized the biofilm of two H. capsulatum strains by metabolic activity, biomass content, and images from scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). We also evaluated the survival rate of G. mellonella infected with both strains under blockage of Hsp60. The results showed that mAb 7B6 was effective to reduce the metabolic activity and biomass of both H. capsulatum strains. Furthermore, the biofilms of cells treated with the antibody were thinner as well as presented a lower amount of cells and extracellular polymeric matrix compared to its non-treated controls. The blockage of Hsp60 before fungal infection of G. mellonella larvae also resulted in a significant increase of the larvae survival compared to controls. Our results highlight for the first time the importance of the Hsp60 protein to the establishment of the H. capsulatum biofilms and the G. mellonella larvae infection. Interestingly, the results with Hsp60 mAb 7B6 in this invertebrate model suggest a pattern of fungus-host interaction different from those previously found in a murine model, which can be due to the different features between insect and mammalian immune cells such as the absence of Fc receptors in hemocytes. However further studies are needed to support this hypothesis